Analyzing the Political Influence of Religious Leaders and Parties: A Case Study of the Tehreek-e-Labbaik Pakistan (TLP) and Its Impact on Pakistan’s Political Landscape - Saddam Hussain,; Prof. Dr. Muhammad Ahsan,; Shahid Sultan, (Dialogue Social Science Review (DSSR), 2025)
This study critically explores the political influence of Tehreek-e-Labbaik Pakistan (TLP), a Barelvi religious-political party that has rapidly transformed Pakistan's socio-political landscape through the strategic use of religious populism, blasphemy politics, and digital mobilization. Grounded in Populism Theory, Framing Theory, and Religious Nationalism, the research investigates how TLP sanctifies its political identity through emotionally charged religious narratives, positions itself as a moral authority, and challenges democratic institutions through performative protests and social media influence.Using thematic analysis, the study reveals nine interconnected themes, including TLP’s demonization of political opponents, ideological penetration beyond electoral success, digital radicalization, and institutional fragility resulting from inconsistent state responses. Findings indicate that TLP not only reshapes political discourse but also threatens civil liberties, pluralism, and internal security by weaponizing blasphemy laws and mobilizing public sentiment through emotionally-driven digital content. The research concludes that TLP's rise reflects deeper institutional weaknesses, sectarian revivalism, and governance gaps. It offers concrete recommendations, including legal accountability, blasphemy law reform, media regulation, civic education, and socioeconomic uplift, to counteract the normalization of religious extremism in Pakistan’s political system. This study contributes to understanding the dynamics of religious populism in South Asia and underscores the urgent need for institutional resilience and democratic reinforcement in the face of rising theocratic nationalism. Keywords: Political Influence, Religious Leaders and Parties, Tehreek-e-Labbaik Pakistan (TLP) , Pakistan’s Political Landscape